Design And Development of Arabic Language Camp For Postgraduate Islamic Studies - Hakim, Amani; Zailani Hj. Ahmad, Suhaila; Abu Bakar, Kaseh (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The Design and Development Research (DDR) approach is an increasingly employed research method by education researchers, as it aims to produce a product through specific stages. Therefore, this study aims to explain and detail the design and development aspects of an Arabic language camp called the Academic Arabic Language Camp (KeMBAA), which utilizes the Design and Development Research approach (DDR). This language camp targets the participation of new postgraduate students in the religious studies department at the Faculty of Islamic Studies, National University of Malaysia. Developing and implementing KeMBAA is an effort to design, develop, and execute a product that incorporates DDR elements such as multidisciplinary and interdisciplinary approaches, mixed methodologies, cycles, and various other components. KeMBAA aims to provide an Arabic language learning experience in an interactive and enjoyable environment for students who are accustomed to traditional Arabic language teaching methods, which require a new touch through more impactful innovation. This study employs the DDR approach, executed through three main phases: the needs analysis phase, the design and development phase, and concluding with the assessment phase. The study's findings present the key features of KeMBAA, alongside the foundational design principles, as an innovation in Arabic language learning for Islamic Studies students. The framework for developing KeMBAA is expected to serve as a reference for Arabic language teaching innovation, particularly for researchers in Arabic and foreign languages.